Multi-impact response of CR4 mild steel: characterising the transition from absorption to failure. (15th March 2023) - Thawani, B; Batchelor, T; Painter, J; Hazael, R; Critchley, R
Abstract: Single impact perforation shots are well understood for various target materials and different shaped projectiles. Although considered a rare case, localised multi-impacts are not well understood as they involve both perforating and non-perforating impacts on the target. The lack of understanding of non-perforating impact on metallic materials makes it tough to predict the change in the material's mechanical performance. Given the widespread use of metallic materials for protective applications, it is important to understand the material response when subject to multiple impacts. To determine the effect of a non-perforating shot on CR4 mild steel and establish a minimum energy impact that will define the transition point whereby the metal can no longer absorb energy a series of impact experiments were conducted. Results show a subsequent perforation event occurs at a lower than the experimentally determined perforation velocity. Results suggest that there could be a direct correlation between the material thickness and the critical crater depth (the depth of crater required to affect the materials ability to absorb energy, the measure of materials performance). As the crater depth increased from 3 mm to 8.5 mm for the first shot, the energy absorption of the steel plate reduced by 25%. This allowed the residual performance for CR4 mild steel to be quantified for a known impact crater, giving a 7% performance loss for every millimetre the critical crater depth grows beyond 3 mm until the point of failure.